Prognostička vrednost inflamatornih biohemijskih markera (IL-KSNUMKS, PCT, CRP) za kardiovaskularne bolesti kod pacijenata sa pankreatitisom: Biochemical Markers Predicting CVD in Pancreatitis - Yang, Zaili; Cui, Dejun; Li, Fei; Huang, Bo; Liu, Qi (Journal of Medical Biochemistry, 2025)
Background: Patients with pancreatitis may be at increased risk of cardiovascular disease (CVD), but the biochemical mechanisms underlying this risk are not fully defined. Inflammatory biomarkers may provide valuable prognostic information. Methods: We retrospectively analyzed 180 patients with pancreatitis (Jan 2021–Dec 2023). Serum levels of interleukin-8 (IL-8), procalcitonin (PCT), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) were quantified using enzyme-linked immunosorbent assay (ELISA) and routine laboratory tests. Logistic regression was applied to identify independent biochemical predictors of CVD, and a risk prediction model was developed and validated using ROC curve analysis. Results: IL-8, PCT, CRP, and age emerged as independent predictors of CVD occurrence in pancreatitis patients (all P<0.05). The biochemical prediction model demonstrated high accuracy, with an AUC of 0.893 in the training set and 0.978 in the validation set. Sensitivity and specificity exceeded 85% across datasets. Conclusion: This study highlights the clinical and laboratory significance of inflammatory biomarkers in pancreatitis. The proposed biochemical model provides a reliable tool for predicting cardiovascular risk and may contribute to improved laboratory-guided risk assessment and patient management.